2018
DOI: 10.1002/ptr.6188
|View full text |Cite
|
Sign up to set email alerts
|

Radix Salviae miltiorrhizae improves bone microstructure and strength through Wnt/β‐catenin and osteoprotegerin/receptor activator for nuclear factor‐κB ligand/cathepsin K signaling in ovariectomized rats

Abstract: Although radix Salviae miltiorrhizae (RSM) is reported to exhibit the antiosteoporotic effect in preclinical study, the underlying mechanism is unclear. To this end, ovariectomized (OVX) rats were employed with administration of RSM (5 g/kg) for 14 weeks.The disturbed serum levels of alkaline phosphatase (ALP), osteoprotegerin (OPG), tartrate-resistant acid phosphatase, and receptor activator of nuclear factor-κB ligand (RANKL) in OVX rats were improved by RSM treatment. Furthermore, supplement of RSM to OVX r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Moreover, the decreased expression of p‐LRP6, IGF‐1, ALP, and OPG were enhanced. While the increased expression of RANKL and CTSK in the tibias and femurs of OVX rats were effectively inhibited by SMB treatment (Liu et al, 2018). Tanshinone VI, extracted from the root of S. miltiorrhiza , which could greatly inhibit osteoclast differentiation and bone resorption by disrupting the formation of actin ring.…”
Section: Natural Chinese Medicinesmentioning
confidence: 99%
“…Moreover, the decreased expression of p‐LRP6, IGF‐1, ALP, and OPG were enhanced. While the increased expression of RANKL and CTSK in the tibias and femurs of OVX rats were effectively inhibited by SMB treatment (Liu et al, 2018). Tanshinone VI, extracted from the root of S. miltiorrhiza , which could greatly inhibit osteoclast differentiation and bone resorption by disrupting the formation of actin ring.…”
Section: Natural Chinese Medicinesmentioning
confidence: 99%
“…Previous investigations have found that Wnt/β‐catenin pathway acts a vital role in regulating many aspects of osteogenesis, osteoblast differentiation, and OP 33,34 . β‐Catenin and C‐myc are both key downstream components of Wnt/β‐catenin pathway, which mediate cell proliferation 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have found that Wnt/β-catenin pathway acts a vital role in regulating many aspects of osteogenesis, osteoblast differentiation, and OP. 33,34 β-Catenin and C-myc are both key downstream components of Wnt/β-catenin pathway, which mediate cell proliferation. 35 The representative Wnt pathway triggers its intracellular signaling by modulating the level of β-catenin within cells and β-catenin subcellular localization.…”
Section: F I G U R Ementioning
confidence: 99%
“…Salvianolic acid A and B modulate osteoblast differentiation and upregulate osteoblast activity [ 24 , 25 ]. Liu et al reported that Radix salviae improves bone microarchitecture and biomechanical properties through the Wnt/β-catening signalling pathway in ovariectomized rats [ 140 ].…”
Section: Other Botanicalsmentioning
confidence: 99%